ENGINEERING-MODELING APPROACH TO BIOTECHNOLOGICAL SYSTEMS - Palomlno l., Alfredo (2001)
In this study we present a systematic approach the modelling of biotechnologycal processes, making use of the concept of hierarchical domains in arder to apply the available modelllng methods. In the same way, aimed at presenting a global vision of the modelling theory, an example is presentad, where we apply the theory described here.